Behavioral methods in consciousness research - Overgaard, Morten (Oxford University Press, 2015)
'Behavioral Methods in Consciousness Research' is the first book of its kind, providing an overview of methods and approaches for studying consciousness. The chapters are written by leading researchers and experts, who describe the methods they actually use in their own studies, along with their pitfalls, problems, and difficulties.--Back cover.